Falling Through the Cracks: Dealing with the Problem of the Unclassifieds in RELTRAD - Burge, Ryan P. (Review of religious research, 2021)
RELTRAD is the most popular and widely used classification scheme for sorting religious traditions in the social sciences, however it struggles with how to sort non-denominational Protestants into one of the existing categories, with a growing number falling into an often ignored “unclassified” category. To demonstrate the growing problem of excluding non-denominational protestants who attend infrequently in the current iteration of RELTRAD. We assess the assumption that the “unclassified” respondents are akin to those who select a “don’t know” option and should be excluded. We also propose several ways to reintroduce low attending non-denominationals back into the larger sample.